Avaliaç\~ao e desafios para o alinhamento do Brasil à normativa da OCDE sobre meio ambiente e clima - Larissa Basso (Instituto de Pesquisa Econômica Aplicada (IPEA), 2023)
– The research evaluates Brazilian alignment to the OECD normative on the environment and climate change. It has three parts. The first describes the trajectory of the accession criteria, indicating how environment and climate change have come to influence the like-mindedness criterion. Given Brazil's role in global environmental governance and the global carbon cycle, they matter for the significative actor and mutual benefits from accession criteria. The second part describes Brazilian advances in aligning with the Committee of Environment Policy, reaffirming and updating the conclusions presented by OECD in 2015 and 2021. The third part presents the political economy of Brazilian environmental and climate regulation focusing land use change and forests. Aligning with OECD requires policy implementation and law enforcement, and coalitions committed to the environmental agenda are crucial to support the process politically.
10419/284903
Keywords: F53; F64; H41; H87; O19; 330; OECD; Brazil; accession; environment; climate